Activación de un SIAL como herramienta para el desarrollo local sustentable: el caso de los productores de berries del Distrito Lagunillas, Michoacán (temporadas 2020 y 2021) - Gómez Bernal, Luis David (Universidad Michoacana de San Nicolás de Hidalgo, 2022)
The main problem of this research has its roots in the fact that since 2015, there is a commercial dependence from berries field producers from the District of Lagunillas, Michoacán towards a transnational corporation which is prevailing in this region and its business model, through which holds a strict control in the value chain in this subsector. This dependence is accompanied by the lack of organization from the producers to find alternative strategies for the merchandising of their products. The main target is to analyze the necessary elements to transit from the current farming model by contract for the production and merchandising of berries to a sustainable local development model starting from the approach of Localized Agri-food Systems (LAS or SIAL in Spanish) and the theory of Sustainable Local Development (SLD or DLS in Spanish) in the District of Lagunillas, (DLAGS) Michoacán, that contributes to the reduction of the productive and commercial dependence of the farmers in this territory. The methodology used in this (for this investigation) is divided into four phases, in the first and the second the actors involved and the force – expectative that they have starting from the construction of a relationships map. In the third, a semi-structured interview was applied during from the months of march to July 2021, it was applied to six key informants from the localities of Morelia, Huiramba and Lagunillas, the fourth phase orders and systematizes the information from the SWOT analysis (FODA in Spanish) and the different arrays derived from it. The results show a weak collective and structural action among the producers, due to factors like organizational mistrust and no cooperation, which prevent the processes of territorializing, which is an indispensable requirement to activate a LAS (SIAL in Spanish) from the mobilization of existent territorial resources and the collective action from the actors in terms of cooperation and solidarity. Therefore, it is stablished a proposal of global strategies form four different dimensions to transit to a Sustainable Located Agri-food System.

El problema principal de esta investigación radica en que desde el año 2015 existe una dependencia comercial de los productores agrícolas de berries del Distrito Lagunillas, Michoacán, hacia una corporación transnacional predominante en esta región y su modelo de negocios, a través del cual ejerce férreo control en la cadena de valor en este subsector, acompañada de la falta de organización de los productores para buscar estrategias alternativas de comercialización. El objetivo general es analizar los elementos necesarios para transitar del actual modelo de agricultura por contrato para la producción y comercialización de berries hacia un modelo de desarrollo local sustentable, a partir del enfoque de Sistemas Agroalimentarios Localizados [SIAL] y teoría del Desarrollo Local Sustentable [DLS] en el Distrito Lagunillas [DLags], Michoacán, que coadyuve a la reducción de la dependencia productiva y comercial de los agricultores en este territorio. La metodología utilizada se divide en cuatro fases; en la primera y segunda se analizan los actores involucrados y la expectativa – fuerza que tienen a partir de la construcción de un mapa de relaciones. En la tercera, se aplicó una entrevista semiestructura durante los meses de marzo a julio del 2021 a seis informantes clave de las localidades de Morelia, Huiramba y Lagunillas. La cuarta fase ordena y sistematiza la información a partir del análisis FODA y las diferentes matrices que de él derivan. Los resultados muestran una débil acción colectiva estructural entre los productores, debido a factores como la desconfianza organizacional y no cooperación, que impiden procesos de territorialización, requisito indispensable para activar un SIAL a partir de la movilización de los recursos territoriales existentes y la acción colectiva de los actores en términos de cooperación y solidaridad. Por ello, se establece una propuesta de estrategias globales desde cuatro diferentes dimensiones para transitar hacia un Sistema Agroalimentario Localizado Sustentable.
Facultad de Economía Vasco de Quiroga. Maestría en Desarrollo y Sustentabilidad
Keywords: info:eu-repo/classification/cti/5; FEVAQ-M-2022-0188; Acción colectiva; Agroindustria; Territorio; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6666